THE ROLE OF MOBILE DEVICES IN DEVELOPING LEARNING MODELS AND STRATEGIES IN MADRASAH EDUCATION - Sa’diyah, Halimatus; Suhermanto, Suhermanto (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The advancement of technology requires us to keep pace with its developments. Today's technology makes everything more modern, practical, and efficient. This research aims to understand our perception of using mobile devices in developing learning models and strategies. Mobile devices play a crucial role in developing learning models and strategies. Moreover, these devices can make the development of learning models and strategies more practical and efficient.This research employs a qualitative approach with a case study method. The results show that the impact of mobile devices is significant and greatly aids in developing learning models and strategies. This makes the learning process easier and more comprehensive. Through mobile devices, students find learning more accessible and can engage in it anytime and anywhere